Preface - Proshchalykin, Maxim Yu.; Legalov, Andrey A.; Loktionov, Valery M. (Zootaxa, 2025)
Doctor of Biological Sciences, Professor, Chief Researcher of the Federal Scientific Center of the East Asia Terrestrial Biodiversity (Far Eastern Branch of the Russian Academy of Sciences), well-known Russian entomologist, good friend, and always a polite and friendly chap, Sergei Yuryevich Storozhenko will turn 70 on November 14, 2025. We are especially excited to present this special volume in his honor.